Exogenous Application of dsRNA for the Control of Viruses in Cucurbits - Delgado-Martín, Josemaría; Ruiz, Leticia; Janssen, Dirk; Velasco, Leonardo (Frontiers in Plant Science, 2022)
The recurrent emergence of viral diseases in intensive horticultural crops requires alternative control strategies. The topical application of double-stranded RNA (dsRNA) molecules homologous to pathogens has been proposed as a tool for virus control in plants. These dsRNAs induce the silencing mechanism, the RNA interference (RNAi), that degrades homologous dsRNAs. Cucumber green mottle mosaic virus (CGMMV) represents a serious threat to cucurbit crops. Since genetic resistance to the virus is not yet available in commercial varieties, we aimed to control this virus by RNAi. For this purpose, we obtained constructions both for expressing dsRNA in bacteria to treat cucumber plants by topical application and for agroinoculation in experiments done in the growth chamber. Besides, greenhouse tests were performed in spring and in summer when plants were challenged with the virus, and differences in several parameters were investigated, including the severity of symptoms, dry weight, total height, virus accumulation, and virus-derived small interfering RNAs (vsiRNAs). Spraying of plants with dsRNA reduced significatively CGMMV symptoms in the plants in growth chamber tests. Agroinfiltration experiments done under identical conditions were also effective in limiting the progress of CGMMV disease. In the greenhouse assay performed in spring, symptoms were significantly reduced in dsRNA-sprayed plants, and the development of the plants improved with respect to non-treated plants. Virus titers and vsiRNAs were clearly reduced in dsRNA-treated plants. The effect of protection of the dsRNA was less evident in the greenhouse assay carried out in the summer. Besides, we investigated the mobility of long (ds)RNA derived from spraying or agroinfiltrated dsRNA and found that it could be detected in local, close distal, and far distal points from the site of application. VsiRNAs were also detected in local and distal points and the differences in accumulation were compared. In parallel, we investigated the capacity of dsRNAs derived from genes of tomato leaf curl New Delhi virus (ToLCNDV), another economically important virus in cucurbits, to limit the disease in zucchini, both by agroinfiltration or by direct spraying, but found no protective effect. In view of the results, the topical application of dsRNAs is postulated as a promising strategy for CGMMV control in the cucumber.